PERSEPSI POTENSI BAHAYA KESELAMATAN DAN KESEHATAN PADA SISWA SEKOLAH DASAR DI TEMBALANG - Ekawati Ekawati; Ida Wahyuni (Kesmas Indonesia, 2023)
Childhood is a time when a person begins to know everything and tends to remember things more easily. The concept of safety and health must be instilled since childhood. The purpose of this study was to describe the perception of potential safety and health hazards in elementary school students. This research is a qualitative research using the Focus Group Discussion method. The informants in this study were 40 students grade 5 from 2 elementary schools in Tembalang sub-district. The results showed that the informants had different perceptions in identifying hazards and the actions to be taken when they were injured. The source of information about the dangers was mostly obtained by informants from teachers and parents. The students have been able to identify potential safety and health hazards well. However, the guidance from parents and teachers is still needed regarding how to control these potential hazards.